HARGA AIR UNTUK IRIGASI PADI SAWAH DI KABUPATEN BADUNG - Sudarma, I Made (Bumi Lestari; Vol 15 No 1 (2015), 2016)
The research was conducted at Badung Regency from May  to  August  2012. Badung Regency determined as the  study  sites intentionally  (purposive  sampling)  with consideration  Badung Regency is utilizing the highest Ayung river water for irrigation than another regencies/city in Bali. Water pricing were  analyzed by the Value Marginal Product (VMP) which derived from equation of the Cobb- Douglas production function.  The analysis showed that the size of area plantation, seed, fertilizer, pesticide, labor and water (irrigation) have real impact on rice production and by using the VMP analysis found that the price of water for irrigation is Rp 314.000/ha/season. The price paid is higher than the water fee for Subak, that is Rp 100,000/ha/season for active members and two-time for inactive members. Even the results of the calculations show that the maximum water price paid by farmers is greater than subak fees, the government can not impose the maximum water pricing approach to the farmers. It is based on the consideration that the agricultural sector is still the sector that needs to be subsidized because it involves the interests of a political, economic, social, cultural and religious.
Keywords: sustainability, paddy rice, production factor, water pricing